2020
DOI: 10.7554/elife.61090
|View full text |Cite
|
Sign up to set email alerts
|

Histone deposition pathways determine the chromatin landscapes of H3.1 and H3.3 K27M oncohistones

Abstract: Lysine 27-to-methionine (K27M) mutations in the H3.1 or H3.3 histone genes are characteristic of pediatric diffuse midline gliomas (DMGs). These oncohistone mutations dominantly inhibit histone H3K27 trimethylation and silencing, but it is unknown how oncohistone type affects gliomagenesis. We show that the genomic distributions of H3.1 and H3.3 oncohistones in human patient-derived DMG cells are consistent with the DNA replication-coupled deposition of histone H3.1 and the predominant replication-independent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 54 publications
(95 reference statements)
3
24
0
Order By: Relevance
“…We next looked at the effect of the H3.3K27M oncohistone on H3K27me3 patterns in the eye. The oncohistone is incorporated into chromatin by histone H3.3-specific chaperones at active promoters and enhancers, and at lower levels by DNA replication throughout the genome [Chan et al, 2013; Piunti et al, 2017; Mohammad et al, 2017; Sarthy et al, 2020], and expression of H3.3K27M in eye discs gives a similar promoter enrichment with background throughout the genome when profiled using an antibody to the K27M epitope (Supplementary Figure 1E). Expression of the oncohistone reduces H3K27me3 staining (Figure 2G,I), and quantitative chromatin profiling of glioma cell lines has previously shown that H3K27me3 is globally reduced but a few domains remain [Sarthy et al, 2020].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next looked at the effect of the H3.3K27M oncohistone on H3K27me3 patterns in the eye. The oncohistone is incorporated into chromatin by histone H3.3-specific chaperones at active promoters and enhancers, and at lower levels by DNA replication throughout the genome [Chan et al, 2013; Piunti et al, 2017; Mohammad et al, 2017; Sarthy et al, 2020], and expression of H3.3K27M in eye discs gives a similar promoter enrichment with background throughout the genome when profiled using an antibody to the K27M epitope (Supplementary Figure 1E). Expression of the oncohistone reduces H3K27me3 staining (Figure 2G,I), and quantitative chromatin profiling of glioma cell lines has previously shown that H3K27me3 is globally reduced but a few domains remain [Sarthy et al, 2020].…”
Section: Resultsmentioning
confidence: 99%
“…The oncohistone is incorporated into chromatin by histone H3.3-specific chaperones at active promoters and enhancers, and at lower levels by DNA replication throughout the genome [Chan et al, 2013; Piunti et al, 2017; Mohammad et al, 2017; Sarthy et al, 2020], and expression of H3.3K27M in eye discs gives a similar promoter enrichment with background throughout the genome when profiled using an antibody to the K27M epitope (Supplementary Figure 1E). Expression of the oncohistone reduces H3K27me3 staining (Figure 2G,I), and quantitative chromatin profiling of glioma cell lines has previously shown that H3K27me3 is globally reduced but a few domains remain [Sarthy et al, 2020]. By profiling eye portions of imaginal discs with oncohistone expression, we find that H3K27me3 still coats domains, although with more dispersion between domains that we attribute to the lower H3K27me3 signal in oncohistone-expressing cells (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…Specific antibodies have been raised against several of these mutations, serving as powerful tools to refine cancer diagnosis. Importantly, the H3.1 and H3.3 point mutations do not affect residues involved in histone chaperone binding and thus do not alter the deposition patterns of these oncohistones into chromatin as shown for the K27M mutation [129,130]. These mutations localize to the N-terminal tails of histones, at or in the vicinity of modifiable residues and affect histone PTMs (methylation and acetylation) through various mechanisms.…”
Section: Point Mutations In Histone Variants (Oncohistones)mentioning
confidence: 91%
“…Noteworthy, even though H3.1 and H3.3 variants can bear identical amino acid substitutions in cancer, there are significant differences between these mutated histone variants. For instance, H3.1K27M and H3.3K27M are differentially distributed in chromatin and H3.1K27M results in stronger reduction of H3K27me3 levels [130]. H3.1K27M and H3.3K27M also promote distinct oncogenic transcriptional programs in diffuse intrinsic pontine gliomas (DIPGs) [120,154] involving variant-specific patterns of active enhancers [143].…”
Section: Cells 2020 9 X For Peer Review 12 Of 33mentioning
confidence: 99%
“…ATRX and DAXX deposit H3.3 in telomeres, imprinted genes and other heterochromatic loci, where it is modified with the trimethlyated lysine 9 heterochromatic mark (denoted H3K9me3) to maintain heterochromatin at these locations ( Drane et al, 2010 ; Elsässer et al, 2015 ; Goldberg et al, 2010 ; Voon et al, 2015 ; Wong et al, 2010 ). The difference between deposition pathways for RC H3.1 and RI H3.3 underlies the more-severe effects of pediatric diffuse midline gliomas caused by H3.1K27M mutations than those caused by H3.3K27M mutations, both of which inhibit global formation of H3K7me3, which normally prevents tumorigenesis ( Sarthy et al, 2020 ).…”
Section: H3 Variantsmentioning
confidence: 99%